Why Is It Advised To Stand In Mahallul Qiyam? (A Semiotic Study Of Narratology) - Siregar, Sri Dewi Priwarti; Sopian, Asep; Nurbayan, Yayan (Universitas Muhammadiyah Gorontalo, 2023)
This study uses a semiotics narrative approach to examine the meaning behind the practice of standing during Mahallul Qiyam when reading the book of Al-Barzanji. The research method used is the analysis of Al-Barzanji text and interviews with several informants who are accustomed to the practice. The results show that the practice of standing during Mahallul Qiyam when reading Al-Barzanji symbolizes the respect and honor of Muslims towards Prophet Muhammad as an example in daily life. In this position, Muslims are invited to reflect on the blessings and virtues given by Prophet Muhammad to mankind. Additionally, this practice also represents the joy and happiness of Muslims in celebrating the presence of Prophet Muhammad in the world, as well as a message of unity among Muslims. By understanding the meaning and message behind this practice, it is hoped that Muslims can deepen their spiritual experience and perform their worship with more devotion and significance. This study concludes that the practice of standing during Mahallul Qiyam when reading Al-Barzanji has a profound meaning and contains many religious and spiritual messages that can be taken by Muslims.